Identification of Loss Factor of Fiber-Reinforced Composite Based on Complex Modulus Method. (19th October 2017) - Li, Hui; Niu, Yi; Mu, Chao; Wen, Bangchun
Abstract : The identification of the loss factor of fiber-reinforced composite based on complex modulus method is presented. Firstly, the damping model of fiber-reinforced composite plate is established, and the relation between each loss factor and modal damping ratio is deduced based on the complex modulus method. Then, the least square relative error function is formed by using the modal damping ratio obtained in the experimental test, and the appropriate step-size is selected in the range of 0 10% to calculate the loss factor. Next, the identification procedure of loss factor of such composite material is summarized, and the corresponding identification procedure is realized based on self-designed MATLAB program. Finally, TC300 carbon/epoxy composite plate is taken as an example to carry out a case study, and its loss factors along the longitudinal, transverse, and shear direction are identified by the complex modulus method. By comparing the measured damping results obtained in this paper and the calculated damping results based on the Adams-Bacon model with the same loss factor, it is found that the corresponding maximum deviation between them is less than 15%, so the correctness of such identification method has been verified indirectly, which can be used to identify loss factor of fiber-reinforced composite with high precision and efficiency.